Effect of heat treatment on the microstructure and mechanical properties of spray formed 7055 aluminum alloy TIG welded joints reinforced by ZrB2/ Al3(Sc, Zr) particles - Ting Huang; Junhua Xu; Lihua Yu; Yubo Jiang; Cheng Li; Lijun Zhao (Journal of Materials Research and Technology, 2023)
Adding high melting point nano-particles to the weld seam is an effective method to improve the thermal crack sensitivity and mechanical properties of aluminum alloy fusion welded joints, and a reasonable heat treatment process will further improve the mechanical properties of the welded joints. In this work, effects of heat treatment on the microstructure and mechanical properties of spray formed 7055 aluminum alloy TIG welded joints reinforced by ZrB2/Al3(Sc, Zr) particles were investigation. The results revealed that the precipitates in S1-SZ7 and S1-Z7 weld seams were η´ phase, and the precipitates in the S1-SZ7 weld seam were smaller, more abundant and dispersed than that in the S1-Z7 weld seam. As a result, the mechanical properties of the S1-SZ7 welded joint were better than those of the S1-Z7 welded joint. Fine grain strengthening, dispersion strengthening, and precipitation strengthening were the reasons for the improvement of mechanical properties of S1-SZ7 welded joints. With the extension of the secondary aging time, the η´ phases in the SZ7 weld seam transformed into η phase, and the precipitated phases gradually became coarse. The mechanical properties of S1-SZ7, S2-SZ7, and S3-SZ7 welded joints gradually decreased.